GMNC risk alleles in individuals with Alzheimer's disease are associated with cerebrospinal fluid concentrations of proteins involved in neuronal plasticity and blood brain barrier function. (20th December 2022) - Visser, Pieter Jelle; Reus, Lianne M.; Gobom, Johan; Teunissen, Charlotte E.; Bertram, Lars; Zetterberg, Henrik; Tijms, Betty M.
Abstract: Background: GWAS studies showed that cerebrospinal fluid (CSF) levels of total‐tau in Alzheimer's disease (AD) are associated with genetic variations in GMNC (Cruchaga, 2013). GMNC is involved in neural progenitor cell differentiation and regulates the generation of multiciliated ependymal cells (Kyrousi, 2015), but the precise role of GMNC in AD pathophysiology remains unclear. We investigated which processes were associated with GMNC risk alleles by studying its associations with CSF levels of 1705 proteins in AD individuals. Method: We selected 432 individuals with abnormal CSF amyloid beta 1‐42 levels from the EMIF‐AD multimodality biomarker discovery study and ADNI. We measured 1705 proteins by untargeted mass spectrometry (EMIF‐AD), the Human DiscoveryMAP panel (ADNI) or targeted mass spectroscopy (ADNI). We correlated the number of GMNC rs9877502‐A risk alleles with protein levels in additive models. To characterise proteins associated with GMNC risk alleles, we performed pathway enrichment analyses for Gene Ontology biological processes (GO‐BP) and ChEA transcription factors. Result: Average age was 71.2 years. At least one GMNC rs9877502‐A risk allele was present in 60% of the AD individuals. Increasing number of GMNC risk alleles was associated with increased total‐tau, as expected, and with increased levels of 591 other proteins (35% of proteins measured). These proteins were associated with neuronal plasticity related processes (table) and SUZ12 and REST transcription factors, which are neuronal transcription repressors (all p‐FDR corrected>6.34e‐18). GMNC risk alleles were further associated with decreased levels of 105 proteins, including 72 proteins associated with blood brain barrier (BBB) permeability. Conclusion: Within AD individuals, GMNC risk alleles are not only associated with increased total‐tau levels but also with increased levels of neuronal plasticity associated proteins. We also found that GMNC risk allele carriers may have less BBB dysfunction than non‐carriers. Further studies are needed to clarify the association of GMNC with neuronal plasticity and BBB function in AD. References Cruchaga, Neuron 2013: 256‐268. Kyrousi, C., Development 2015: 3661‐3674.